Literasi Qira'ah Teks Arab Bertema Lingkungan dan Kontribusinya Terhadap Pemahaman Etika Konservasi Alam - muhamad_ridwan fauzi (Envirology, 2024)
Abstract Qira'ah literacy is one of the essential competencies in Arabic language learning that aims not only to improve students' ability to read and comprehend Arabic texts but also to serve as a medium for instilling Islamic values in everyday life. One relevant theme that can be integrated into qira'ah learning is environmental issues, considering that various problems such as pollution, deforestation, water scarcity, climate change, and waste management require collective awareness and responsibility. This study aims to analyze the contribution of qira'ah literacy to the understanding of environmental conservation ethics through the study of Arabic texts on environmental themes from an Islamic perspective. The research employed a literature review method by examining Qur'anic verses, the Hadith of the Prophet Muhammad (peace be upon him), Qur'anic exegesis, books, official documents, and scientific articles related to qira'ah learning, Islamic education, environmental ethics, and sustainable development. The data were analyzed using a content analysis approach to identify environmental conservation values embedded in Arabic texts and relate them to the principles of Islamic environmental ethics. The findings indicate that qira'ah literacy contributes to improving Arabic reading comprehension while strengthening students' understanding of the concepts of khilāfah (stewardship), amānah (trust), tawḥīd (the oneness of God), and mīzān (balance) as the foundations of environmental conservation ethics in Islam. Furthermore, the use of Arabic reading texts on nature conservation, waste management, water preservation, and tree planting successfully integrates linguistic competence with the development of environmentally responsible character. The study also demonstrates that Islamic environmental values are closely aligned with the principles of sustainable development. Therefore, qira'ah learning can serve as an effective educational strategy for developing Arabic language proficiency, ecological awareness, and moral responsibility toward environmental conservation based on Islamic values.